Analysis of tumor-infiltrating exhausted T cells highlights IL-6 and PD1 blockade as a combined immunotherapy strategy for non-small cell lung cancer - Lulu Zhang; Lulu Zhang; Xiyuan Guo; Xiyuan Guo; Xiaoke Sun; Jue Liao; Qin Liu; Yingchun Ye; Zhihui Yang; Ratchada Cressey; Qing He; Qing Yuan; et al. (Frontiers in Immunology)
ObjectiveGiven the limitations of immunotherapy for treating non-small cell lung cancer (NSCLC), we investigated the phenotype and function of exhausted CD8+T cells and analyzed a novel combination immunotherapy to restore the effector killing function of tumor-infiltrating CD8+T lymphocyte (TIL).MethodsWe examined the expression and function of immunosuppressive molecules on CD8+T cells of peripheral blood mononuclear cells (PBMCs) and TILs by using prospectively collected peripheral blood, pleural effusions, and tumor tissues from patients with NSCLC and correlated the results with clinical data. We then evaluated the effect of interleukin 6 (IL-6) stimulation on CD8+T cells. Finally, we assessed the effects of combined blockade of PD1 and IL-6 on macrophage recruitment in a zebrafish macrophage model and CD8+ T cell function and tumor growth in PBMC humanized mouse model.ResultsThe expression of exhaustion markers on CD8+ T cells was found to be notably higher in both tumor and paraneoplastic tissues compared to peripheral blood. Furthermore, the degree of CD8+ T cell exhaustion exhibited a progressive increase with proximity to the tumor. When CD8+ T cells from peripheral blood and tumor tissues of NSCLC patients were stimulated with IL-6, the expression level of exhaustion markers, especially PD1, was further elevated. In the in vitro experiment, the combined inhibition of IL-6 and PD1 substantially enhanced the effector killing function of CD8+ T cells in NSCLC pleural effusion samples. In a macrophage-labeled zebrafish model, combined blockade of IL-6 and PD1 enhanced the recruitment of macrophages. In PBMC humanized mouse model, combined blockade of IL-6 and PD1 enhanced the inhibition of tumor growth.ConclusionOur data suggest that CD8+ T cells in NSCLC patients were in a state of exhaustion and combined blockade of IL-6 and PD1 to restore CD8+ T cell function to inhibit tumor growth may be an effective clinical strategy for the treatment of NSCLC.